Positive solutions for a system of difference equations with coupled multi-point boundary conditions. Issue 2 (1st February 2016) - Henderson, Johnny; Luca, Rodica
Abstract : We investigate the existence and nonexistence of positive solutions for a system of nonlinear second-order difference equations with parameters subject to coupled multi-point boundary conditions.